2012
DOI: 10.7120/096272812799129466
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitudes to animal welfare and rights in Europe and Asia

Abstract: A survey of attitudes towards the welfare and rights of animals was conducted in universities in 11 European and Asian countries, to improve understanding of cultural differences that might impact on trade and international relations. Collaborators' universities were recruited in each country to assist in the design, translation and administration of the survey via the internet in a convenient selection of the country's universities, providing 3,433 student responses from at least 103 universities. Respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
101
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 17 publications
20
101
3
4
Order By: Relevance
“…In contrast to some recent studies, which reported that religion was not a significant predictor of public attitudes toward animals (and animal products) (Izmirli & Phillips, 2011;Phillips et al, 2012), our results demonstrate a significant negative correlation between Christianity as a source of inspiration and attitudes toward animals. Specifically, respondents who reported that inspiration source was Christianity showed less concern for animals than those who reported otherwise.…”
Section: Religion and Pet Ownershipcontrasting
confidence: 56%
See 2 more Smart Citations
“…In contrast to some recent studies, which reported that religion was not a significant predictor of public attitudes toward animals (and animal products) (Izmirli & Phillips, 2011;Phillips et al, 2012), our results demonstrate a significant negative correlation between Christianity as a source of inspiration and attitudes toward animals. Specifically, respondents who reported that inspiration source was Christianity showed less concern for animals than those who reported otherwise.…”
Section: Religion and Pet Ownershipcontrasting
confidence: 56%
“…Respondents were asked to respond to each question on a 5-point Likert scale, ranging from 1 (extremely acceptable) to 5 (extremely unacceptable). A higher score on the AIS indicates greater concern for the welfare of animals (Phillips et al, 2012). Examples of items include: "Using animals for work"; "Marking animals by branding or ear notching"; "Depriving animals of their needs for food and water"; "Controlling wildlife populations by killing."…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Greater tolerance to not stunning the chicken for religious reasons was evident in higher income respondents, confirming previous findings in Chinese respondents [43]. A greater willingness to recognise poor welfare on farm and during transport in high income respondents may reflect a greater ability to pay for high welfare products.…”
Section: Age Income and Educationsupporting
confidence: 77%
“…They were also much more likely to buy processed products, which may reflect their role in managing the nutrition of children. They reported buying less chicken than males, confirming a Eurasian survey which found that female students reported that they ate poultry less commonly than male students [43]. Males' greater interest in seeing information regarding the welfare of chicken at the point of sale than females and even being more prepared to pay for this conflicts with other studies [44,45] which found that females were willing to pay extra for certified food products.…”
Section: Gendercontrasting
confidence: 54%